Adapting and Applying the Phenice (1969) Adult Morphological Sex Estimation Technique to Subadults1. Issue 3 (6th February 2017) - Klales, Alexandra R.; Burns, Tesa L.
Abstract: This research evaluated whether adult morphological sex estimation methods of the innominate could be adapted and applied to subadults. The subpubic concavity, described by Phenice (1969) and revised by Klales et al. (2012), was modified for use with subadults. Two observers scored radiographic images from the PATRICIA database of 334 individuals of both sexes aged between 1.19 and 20.47 years. Score frequencies shifted from score 2 (straight) to higher frequencies of score 3 (convexity) in males and score 1 (concavity) in females with increasing age. Using ordinal logistic regression, sex classification was highest for the oldest age cohort at 97.2% and then decreased by age cohort. Interobserver error rendered a high level of agreement (0.806) using the intraclass correlation coefficient. Results indicate that the Klales method can be modified and applied to subadults to accurately estimate sex following the onset of puberty with a high degree of reliability and validity.